Toxicity study of Zingiber officinale volatile oil as antifilariasis in mice and rats - Budi Mulyaningsih, Budi Mulyaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: The volatile oil of Zingiber officinale has been reported effective to reduce microfilariae in Fells catus, L. According to the fact, there is chance that the volatile oil can be developed for treatment of filariasis in man. Before that idea can be realized some toxicity studies of Zingiber officinale should have to be done. Objective: This study was designed to know the potency of the acute and chronic toxicity in rodent. Methods: Acute toxicity study was perfomed in mice and rat as experimental animal and subchronic toxicity study was done only in mice. This study was done in standard methods.Results: The LD 50 value (mean ÃÂ± SD) of Zingiber officinale volatile oil in mice was 8.051 ÃÂ± 1.254 ml/Kg BW., while in rat the value was 12.99 ÃÂ± 1.021 ml/Kg BW. Routine hematology analysis showed that no significant difference between the control and the experimental groups.Conclusion: The mechanism responsible in the death of the experimental animal in this toxicity study, seems to be the ability of the volatile oil to produce contraction of the smooth muscle especially in the airway system (trachea).Key words : microfilariae - filariasis - acute toxicity - Fells catus - chronic toxicity.